Ethnic conflict in India : a case-study of Punjab - Gurharpal Singh (London, 2000)
This important new book critically evaluates the conventional reading of ethnicity and ethnic conflict in contemporary Indian politics. By focusing on India's nation and state-building in the peripheral regions since 1947, in particular Punjab, it argues that there is a case for considering India as an ethnic democracy.
Keywords: Communalism-India-Punjab-Case studies